Characteristics of antibiotic sensitivity of Staphylococcus aureus isolated from dairy farms in Ukraine - BerhilevychO. М.; Kasianchuk, V. V.; Kukhtyn, M. D.; LotskinI. М.; Garkavenko, T. O.; Shubin, P. A. (Regulatory Mechanisms in Biosystems, 2017)
Staphylococcus aureus is one of the most important microorganism in the process of raw milk production and has significance for people’s health as it causes dangerous microbial contamination of dairy production. Furthermore, raw milk and the environment of livestock farms may be potential vehicles for distribution of antibiotic-resistant strains of S. aureus. The aim of the present study was to establish antibiotic sensitivity profiles of S. aureus depending on its origin from dairy farms, with a special focus on methicillin-resistant isolates. A total of 165 samples were collected for investigation in the period 2014–2016 from 5 dairy farms in Ukraine. All samples were analyzed for the presence of S. aureus using the Baird Parker Agar with Egg Yolk Tellurite Emulsion. Typical staphylococcal colonies were examined morphologically and for presence of coagulase and hemolysin activities. From these, positive samples for S. aureus were 62 (37.6%): 4 (6.5%) raw milk, 17 (77.4%) swabs of udder skin, 18 (29.0%) milk from cows with subclinical mastitis and 21 (33.9%) environmental samples. The standard disk diffusion method was used to determine sensitivity of S. aureus isolates to 10 antibiotics. The antimicrobial sensitivity profiles of S. aureus isolates showed differences between them, which depends on the origin of the isolates. Our results demonstrated that most of S. aureus isolates were resistant to penicillin, oxacillin and vancomycin. Of the 62 S.aureus isolates, 20 (32.3%) and 5 (8.1%) were found to be multiresistant to 3 different antibiotics, 6 (9.8%) isolates to 4 antibiotics, 12 (19.4%) and 3 (4.8%) to 5 antibiotics (P10, OX1, VA5, L10, TE30 and P10, OX1, VA5, CIP10, TE30 respectively). All isolates resistant to penicillin and oxacillin were typed by mec A gene in PCR with two primers (MecA147-F and MecA147-R). The results show that 66.7% of these isolates yielded a mecA product. The information obtained from this study is useful for understanding the prevalence of S. aureus and its antibiotic sensitivity in dairy farms and can be useful for local and national monitoring or for designing specific control programs of methicillin- and multiresistance isolates present in the food chain of milk production.